Structure Modification of Ethyl p-methoxycinnamate Isolated from Kaempferia galanga Linn. and Citotoxicity Assay of The Products on WiDr Cells - Ekowati, Juni; Rudyanto, Marcellino; Sasaki, Shigeru; Budiati, Tutuk; Sukardiman, .; Hermawan, Adam; Meiyanto, Edy (Indonesian Journal of Cancer Chemoprevention, 2010)
Ethyl p-methoxycinnamate, major ingredient of Kaempferia galanga rhizome, have been reported not only has analgesic Ã¢â¬â anti inflammatory activities like NSAIDs which inhibited cyclooxygenase, but also inhibit tumor cell proliferation in specimen of mouse epidermis. Therefore, it will be interesting to carry outÃÂ  synthetic studies on the derivates of ethylÃÂ  p-methoxycinnamate and searching their citotoxic activity on WiDr cell. We wish to report of structure modification on carboxyl moiety ofÃÂ  ethyl p-methoxycinnamateÃÂ  andÃÂ  evaluation on their citotoxic activityÃÂ  on WiDr cell. Isolation of ethyl p-methoxycinnamate from Kaempferia galanga rhizome was carried out by percolation with ethanol 96% as solvent. Hydrolysis of ethyl p-methoxycinnamate in basic condition was performed to obtain p-methoxycinnamic acid. Preparation of some thiourea derivates of ethylÃÂ  p-methoxycinnamate was carried outÃÂ  by microwave irradiation. Citotoxicity assay was carried out by MTT method for 48 h. ÃÂ  ModificationÃÂ  ofÃÂ  carboxylÃÂ  groupÃÂ  ofÃÂ  ethylÃÂ  p-methoxycinnamate to its thiourea form could be carried out by microwave irradiation gave; (E)-3-(4-methoxyphenyl)-N-(phenylcarba- mothioyl)acrylamide (50%); (E)-3-(4-methoxyphenyl)-N-(4-methoxyphenylcarbamothi- oyl)acrylamide (26%) and (E)-3-(4-methoxyphenyl)-N-(4-methylphenylcarbamothioyl) acrylamide (54%), yield calculated for 2 step from the acid chloride. All compounds showed no citotoxic effect on WiDr cell at 48 h incubation.